2017
DOI: 10.17214/gaziaot.327867
|View full text |Cite
|
Sign up to set email alerts
|

Fracture load of ceramic crowns supported by some novel anchoring dental systems

Abstract: OBJECTIVE: This study aimed to evaluate the fracture load of endocrown restorations and fiber-reinforced composites (FRCs) fabricated through computer-aided design/ computer-aided manufacturing (CAD-CAM) for postcores of anterior teeth. MATERIALS AND METHOD: Forty post-core-supported crowns and endocrowns were fabricated through CAD-CAM on a canine root zirconia model (Ice Zirconia, ZirkonZahn GmBH, Bruneck, Italy). The static load-bearing capacity was measured on the following restoration groups: Group 1: zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…SEM observation shows that there is no significant difference between the strength of the ceramics and composite bond among the samples treated with HF acid and sandblasting. However, significant difference was recorded in the microstructure of the surface in Vita Enamic, Lava Ultimate and Cerasmart materials after the treatment [24].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…SEM observation shows that there is no significant difference between the strength of the ceramics and composite bond among the samples treated with HF acid and sandblasting. However, significant difference was recorded in the microstructure of the surface in Vita Enamic, Lava Ultimate and Cerasmart materials after the treatment [24].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the bond between the conventional ceramics and composite cement, which shows fracture on the seal between ceramic and composite, in hybrid materials different results can be observed. Cekic-Nagas and associates [24] observed the lost of bond in 39% of samples Vita Enamic and composite cement inside the hybrid material due to the cohesive structural damages of the material, while cohesive fractures were not registered in Cerasmart samples. The bond strength was high in cohesively fractured samples.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…19,20 Endocrown is a monoblock restoration achieved by combining the intraradicular post, the core, and the crown in one component can reduce number of adhesive interfaces that are prone for debonding. 21 According to Biacchi et al, lithium disilicate ceramics have shown greater resistance to compression forces in endocrown restorations, compared with traditional crowns supported on fiber posts. CAD-CAM ceramics such as, lithium disilicate reinforced ceramics, appear to be the best option for anterior tooth endocrown restorations.…”
Section: Discussionmentioning
confidence: 99%
“…72 Farklı endokron materyalleri ile fiber postların karşılaştırıldığı bir çalışmada (CAD-CAM ile üretilen tek parça fiber post-kor sistemi (deneysel CAD-CAM fiber blok); fiberle güçlendirilmiş kompozit post; zirkonya endokron ve lityum disilikat seramik endokron); endokron monoblok restorasyonların, fiberle güçlendirilmiş post-korlara alternatif olabileceği bildirilmiştir. 73…”
Section: Polietereterketon (Peek)unclassified